Mother-to-Child Transmission of HIV Within 24 Months After Delivery in Women Initiating Lifelong Antiretroviral Therapy Pre/Post-Conception or Postnatally; Effects of Adolescent Girl and Young Woman Status and Plasma Viremia Late in Pregnancy - Duri, Kerina; Mataramvura, Hope; Chandiwana, Panashe; Mazhandu, Arthur John; Banhwa, Simeon; Munjoma, Privilege Tendai; Mazengera, Lovemore Ronald; Gumbo, Felicity Zvanyadza (Frontiers in Virology, 2022)
Introduction Mother-to-child-transmission (MTCT) of HIV can occur in pregnancy/in utero (IU), during childbirth/intrapartum (IP) or postpartum (PP) through breastfeeding from an infected mother to her infant. Burden of PP-MTCT and associated risk factors remain poorly described, especially in adolescent girls and young women (AGYW) aged 15-24-years. Furthermore, despite concerns on high postnatal-seroconversions, there is paucity of data on the burden of subsequent MTCT rates. Methods Pregnant women ≥20 weeks of gestation were enrolled into the University-of-Zimbabwe-Birth-Cohort from four primary-health-centres in Harare, Zimbabwe. Mother-infant-dyads were followed up from delivery, week(s) 1, 6, 10, 14, 24, 36, 48, 72 and 96 after birth. Women who were uninfected at baseline were re-tested for HIV on subsequent visits. Plasma-HIV-RNA was quantified using reverse-transcriptase-polymerase-chain-reaction. Exposed babies were tested for HIV using qualitative/quantitative proviral-DNA-PCR on dried-blood-spots. Maternal-infant factors were tested in univariable/multivariable regression analyses for HIV-MTCT predictors. Results 600 HIV-uninfected and 608 HIV-infected pregnant women on Tenofovir/Lamivudine/Efavirenz regimen were enrolled from 2016-2019. Postnatal-HIV-incidence was 0.42 cases/100-women-years [95% confidence-interval (CI): 0.12-1.1]. Postnatal-seroconverters were less likely to have children/pregnancies sharing same father and unaware of their spouses/intimate-partner’s HIV-status: p=0.008 and p=0.02, respectively compared to non-seroconverters. Overall HIV-MTCT-rate was (15/549): 2.7%(CI:1.3-4.1%); (7/93)7.5% observed in AGYW against 1.7%; in women aged >24, p=0.008. PP-MTCT was the predominant 9/15(60%) route, followed by IP-MTCT 4/15(26.6%), whilst IU and postnatal-MTCT-rates each contributed 6.7% of all infant infections. Postnatal-MTCT incidence was 12.8 CI:(0.3-71.4) infant HIV-infections/100-child-years of breastfeeding; a rate 14-times higher than PP-MTCT rate in babies born to women HIV-infected pre/post-conception whose babies were HIV-DNA-PCR-negative at six weeks. Antenatal HIV-RNA >1000 copies/mL was independently associated with MTCT; odds ratio (CI):9.3(2.6-43.1). Infected infants’ pre-HIV-treatment HIV-RNA levels correlated positively with maternal viral load, Spearman-Rank-correlation; r=0.6;p=0.03. Discussion Mothers were 9.3 times more likely to transmit if HIV-RNA was >1000 copies/mL, disproportionately occurring in vulnerable AGYW. Breastfeeding associated PP-MTCT remains high, therefore it’s imperative that HIV-infected women commence antiretroviral-therapy early in pregnancy, suppress HIV-RNA until weaning to decrease the risk of MTCT, and possibly reduce the severity of disease in infected infants. HIV-uninfected lactating mothers should be continuously counselled on the risks of postnatal-seroconversion. www.clinicaltrials.gov,trial registration number: NCT04087239.